Corporate Governance dan Tax Avoidance pada Perusahaan Pertambangan - Sulardi, Sulardi; Pramudya, Richard Arya (Jurnal Akuntansi dan Bisnis, 2024)
This research aimed to determine the effect of corporate governance, which is proxied by the proportion of independent commissioners, managerial ownership and institutional ownership, on tax avoidance in mining sector companies listed on the IDX during the 2018-2022 period. The research sample comprised 14 companies, with 70 observations from the purposive sampling method. The company’s annual report data was analyzed using the multiple linear regression method, SPSS. Research findings show that the proportion of independent commissioners is not proven to influence tax avoidance. On the other hand, managerial ownership shows a significant negative effect on tax avoidance, while institutional ownership shows a significant positive effect on tax avoidance.